Effects of polypropylene mesh on the component separation technique in complex incisional hernia surgery (Annals of Medical Research, 2021)
Aim: Giant or complex hernia repair is an important risk factor for poor outcome compared with results after repair for smaller hernias. Various operation techniques have been described for this hernia types. In this study, we aimed to present our outcomes of component separation technique (CST) repair in patients with giant incisional hernia and compare the results of CST with or without mesh.Material and Methods: A comprehensive retrospective study was planned and performed on all patients who underwent the CST for complex incisional hernia between 2007 and2013 at study institution. Patients were divided into two groups according to polypropylene mesh use. Follow-up appointments were typically done at 2 weeks, 4 weeks, 2 months, 3 months, 6 months, 1 year and 2 years. Hernia recurrence was diagnosed by physical examinations and ultrasonography if needed.Results: A total of 91 patients were evaluated in this study, with 45 (49.4%) men and 46 (50.6%) women. The median age was 55(23-83) years and hernia defect size was 314 cm2 (62-940 cm2). Component separation group (CS) consisted of 13 women and 10 men with median age 56 years, whereas Component separation with mesh group (CS-M) comprised 35 women and 33 men with median age 55 years. A total of three patients (13%) had recurrence hernia in CS group vs. none of patients in CS-M group (p=0.015). Surgical site complication developed in 8 (34.7 %) patients in CS group, whereas in 28 (40.5%) patients in CS-M group (p=0.66). Statistical significant factors were associated with the development of complications including male gender (p=0.032), older than 60 years (p=0.045), and ASA score was 3 (p=0.017).Conclusion: Component separation technique could be preferred by surgeons in complex ventral hernias. Contrary to common belief, onlay polypropylene mesh placement was not increase the surgical site complications. Also, recurrence rates were lower in mesh group statistically significantly.
Keywords: Component separation technique; complex incisional hernia; polypropylene mesh; herniography